2020
DOI: 10.3390/ijerph17176343
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness, Exercise Self-Efficacy, and Quality of Life in Adulthood: A Systematic Review

Abstract: Background: The aim of the present work is the elaboration of a systematic review of existing research on physical fitness, self-efficacy for physical exercise, and quality of life in adulthood. Method: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines, and based on the findings in 493 articles, the final sample was composed of 37 articles, which were reviewed to show whether self-efficacy has previously been studied as a mediator in the relationship bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 80 publications
(252 reference statements)
3
13
0
1
Order By: Relevance
“…Our results also suggest self-efficacy significantly contributes to runners’ life satisfaction. A high degree of self-efficacy contributes to perseverance and to feeling positive and energetic [ 21 , 22 ], all of which are important to leading a healthy and satisfying life [ 23 , 24 , 53 ]. More importantly, our results extend earlier work by finding that flow experience had an indirect effect on the relationship between self-efficacy and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also suggest self-efficacy significantly contributes to runners’ life satisfaction. A high degree of self-efficacy contributes to perseverance and to feeling positive and energetic [ 21 , 22 ], all of which are important to leading a healthy and satisfying life [ 23 , 24 , 53 ]. More importantly, our results extend earlier work by finding that flow experience had an indirect effect on the relationship between self-efficacy and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, the stronger an individual’s self-efficacy and outcome expectation, the more likely he or she will begin and persist with a given activity [ 21 ]. During exercise, people with a higher level of self-efficacy were usually found to show a greater sense of energy, expend less effort, and experience more positive feelings [ 22 ]. Recent studies have found that general self-efficacy was strongly related to college students’ life satisfaction [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also in a recent review, sport scientists examined the potential mediating role of self-efficacy in the relationship between physical fitness and well-being. They could confirm that both fitness and self-efficacy play an important role for improved health, however, the causal relations remain unclarified [ 89 ]. This illustrates that more studies are needed to establish whether self-efficacy promotes physical activity or the other way around.…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish version of the SF-36 [ 46 ] questionnaire was used, which has proven validity, high reliability, and wide use in the older adult population for measuring their subjective health and capabilities or limitations to perform daily tasks [ 42 , 46 , 47 ]. It is composed of eight domains: physical function (PF, 10 items, α = 0.93), physical role (PR, 4 items, α = 0.95), bodily pain (BP, 2 items, α = 0.87), general health (GH, 5 items, α = 0.79), vitality (VI, 4 items, α = 0.85), social function (SF, 2 items, α = 0.72), emotional role (ER, 3 items, α = 0.91) and mental health (MH, 5 items, α = 0.85).…”
Section: Methodsmentioning
confidence: 99%